With Regard to the Connection between Pedagogical Schools and High Schools in Teacher Training and Retraining in Vietnam - Thi Bich, Asso. Pro and Dr. Truong; Khuong, Dr. Nguyen Duc (RA Journal of Applied Research, 2023)
In teacher training and retraining, the close connection between pedagogical schools and high schools is one of the important factors, which is not only meaningful in deciding the quality of trained teachers, but also meaningful in the professional development process of teachers themselves during the time they practice education in high schools. The article mentions measure to link pedagogical schools with high schools in developing professional competencies for teachers to meet the requirements of educational innovation in the current context in Vietnam. That is to build a legal basis between the pedagogical school and the high school in organizing students to practice pedagogy and retrain teachers; is to build a partnership in professional development for teachers; is to build relationships in the organization of practice improvement studies.